Analisis Penyebab Terjadinya Penumpukkan Berkas Rekam Medis di Ruangan Filling pada Rumah Sakit X Batam Kota Tahun 2022 - Fani Farhansyah; Desfa Anisa; Ira Safitri (Yayasan Literasi Sains Indonesia, 2023)
Inpatient and outpatient medical record files at X Batam City Hospital have increased the number of medical record files, because every year the number of outpatient and inpatient visits at X Batam City Hospital has increased significantly, so that the medical record file storage area is also narrower too. The purpose of this research is to find out the causes of the accumulation of medical record files in the Filling Room at X Batam City Hospital. The research method used in this study uses a qualitative method by taking data from observations, interviews and documentation. The results of this study indicate that the cause of the accumulation of medical record files is that officers have never participated in medical record training so that the lack of knowledge from medical record officers regarding the storage of medical record files and shelves in the filling room at X Batam City Hospital is not in accordance with the SOP. The medical record file storage system at X Batam City Hospital is placed in one room where the storage system uses a centralized system. Aspects that cause the accumulation of medical record files in the filling room at X Batam City Hospital, namely for the first aspect are medical record officers, the second aspect is infrastructure suggestions and the third aspect is Method.